Uptake, utilization, and satisfaction with employer sponsored health insurance in a population of vineyard farmworkers - Malcolm Hobbs; Monica Cooper (California Agriculture)
California farmworkers experience lower health outcomes and underutilize health services compared with the general population, impacting their well-being and farm productivity. Employer sponsored health insurance facilitates access to health services and represents one method for improving farmworker health outcomes, but more knowledge is needed to promote employee uptake and utilization. From 2021 to 2023, we surveyed 497 vineyard workers in Napa County on their views of health insurance. Offering insurance has a large impact on benefits satisfaction. However, satisfaction is limited and uptake low when employers contribute less than 80% to the annual premium. This is principally because when the cost to them is greater, farm employees opt out of health insurance to avoid wage reductions to prioritize other essential living costs. Seasonal workers opt out at especially high rates because they are offered the lowest employer premium contributions and are simultaneously the lowest earners.